Is it feasible to screen older drivers using a battery of available tests and triage them into meaningful driving risk groups?. (1st March 2011) - Jones, V; Gielen, A; Rebok, G; Bailey, M; Parrish, J; Gaines, J; Shao, Y L
Abstract : By 2030 the older population aged 60 and above is projected to be twice as large as any other age-group, growing from 35 million to 71.5 million and representing nearly 20% of the total U.S. population. Coupling this growth with an increase in life expectancy, we can expect substantial increases in the number of older Americans travelling on our roadways. Older driver crashes are related to inattention or slowed response, lack of recognition of these changes or the fact that they can be influenced by prescription medication use, poor vision or other medical conditions. The presence these changes may not constitute heightened risk except in a driver who fails to adjust their behaviour to compensate for those conditions. We do not have good measures of elevation in risk, and we have limited evidence upon which to make recommendations to older drivers about how to regulate their driving behaviours. Is it feasible to screen older drivers using available tests and triage them into meaningful driving risk groups? This study presents a description of more than 60 older adults ages 65 and older who are being screened for possible participation in a comprehensive driver-self regulation training program. Components of the screening include vision, range of motion, reaction time measurement, and functional cognitive testing. Preliminary results suggest that up to 30% of these individuals may screen at high driving impairment risk.